Proteômica comparativa das cepas 9a5c e fb7 de xylella fastidiosa - Souza, Jessica Brito de (2017)
Xylella fastidiosa is a gram-negative and non-flagellate bacterium that colonizes the xylem of various cultivated and wild plants worldwide. In the last decades, it has been well studied due to the importance of this phytopathogen as the causing agent of two major diseases, Citrus Variegated Chlorosis (CVC) in Brazil and Argentina, and Pierce Disease (PD) in the United States. Some strains of X.fastidiosa have their genomes completely or partially elucidated, such as 9a5c, isolated from orange in the state of São Paulo, and the strain Fb7, isolated from orange in the region of Corrientes in Argentina. Based on the genomic analysis between strains 9a5c and Fb7, and on the importance of a lipase/esterase in the pathogenicity of X.fastidiosa, the objective of this work was to analyze and identify the factors associated with the pathogenicity and virulence of X.fastidiosa strain 9a5c and Fb7. To visualize the presence of LesA in the total and secreted protein samples of strains 9a5c and Fb7, esterase and lipase tests were performed. Lipase activity was analyzed by culturing the bacteria in culture medium supplemented with 1% tributyrin. This test demonstrated activity under the short chain triacylglycerols present in the medium and can be visualized by the increased halo formation in the Fb7 strain. The esterase activity, determined by the substrate 4-methylumbelliferylbutyrate (4-MUB), showed significant and clearly expressed values. Hence, the Fb7 strain showed considerably higher activity when compared to 9a5c. In search for virulence factors, a liquid chromatography coupled to mass spectrometry (LC-MS / MS) of the total proteins of the X.fastidiosa cultures of both strains was performed. In this analysis, it was identified 119 differentially expressed proteins. Among them, some proteins with functions associated with bacterial virulence were overexpressed in Fb7 strain, compared to 9a5c strain. The RT-qPCR analysis allowed to validate the expression of some of these proteins. The results showed that LesA and other proteins with higher levels of expression in Fb7 play an important pathogenicity role in this strain. Thus, they are factors that may explain the greater virulence of Fb7 strain when compared to strain 9a5c.